Patients’ characteristics, Cytochrome P4501A1 genetic polymorphisms and breast cancer risk in Sudanese women - Fatima Hamad (AOSIS, 2021)
Background: The CYP1A1 catalyses polycyclic aromatic hydrocarbons activation to reactive metabolites, causing deoxyribonucleic acid (DNA) damage and cancer. It is highly polymorphic and displays ethnic differences in various populations.